Developing Intercultural Communicative Competence: Formative Assessment Tools for Mandarin as a Foreign Language: Formative Assessment Tools for Mandarin as a Foreign Language (Malaysian Journal of Learning and Instruction, 2019)
Purpose - Intercultural communicative competence (ICC) is important in intercultural exchange, to address problems and conflicts which may arise due to miscommunication that results from interlocutorsâ€™ diverse cultural and linguistic backgrounds. Interlocutors may have different perceptions and interpretations of communicative behaviour. However, cultural and intercultural aspects seem to be ignored in teaching Mandarin as a foreign language (MFL) in Malaysian higher education institutions. Hence, the ICC level among local MFL learners is unknown. In this study, formative assessments were designed in a culturally integrated MFL module to investigate learnersâ€™ level of ICC in a selected Malaysian polytechnic.Methodology - The polytechnic was selected as cultural competency was incorporated in the MFL course. A design and developmental research was carried out to design formative assessment for ICC based on expertsâ€™ feedback. The assessment comprised Intercultural Discussion and Reflections, Cultural Discovery, Cultural Quizzes and an Intercultural Communicative Task.  They were implemented to assess learnersâ€™ ICC.Findings - The results indicate that different forms of assessment were suitable for assessing the respective competences, and that multiple forms of formative assessment should be employed to assess and improve MFL learnersâ€™ ICC.Significance - Instructors in higher education could apply these forms of formative assessment to develop ICC among their MFL learners. The assessments could also be extended to intercultural communication competence development in other languages, which is important in a multicultural and globalized society.